A SHOCK-RESPONSIVE SOCIAL PROTECTION SYSTEM: ANALYSIS FRAMEWORK - Yarmaloyan, Marine (Journal of Sociology: Bulletin of Yerevan University, 2024)
The paper discusses the concept of a "shock-responsive social protection system", the main options for shock-responsive social protection: including design tweaks, piggybacking, horizontal and vertical expansions, and alignment. Some key criteria are discussed in terms of evaluating the ability of social protection system to respond to emergencies. Some conclusions are presented as offers in terms of preparing for an effective response to shocks as well.